24-Epibrassinolide Enhanced Plant Antioxidant System and Cadmium Bioavailability Under Soil Cadmium Stress - Wenle Song; Hongen Li; Ziyi Zhao; Rongrong Si; Wen Deng; Mengqi Wang; Yepu Li (Plants)
Soil cadmium pollution poses significant environmental risks, prompting global concern. Previous studies have demonstrated that 24-epibrassinolide (Brs) can enhance plant photosynthesis, thereby potentially improving the efficiency of soil cadmium remediation by increasing biomass. Therefore, this study investigated the use of Brs to enhance Cd remediation by willow and alfalfa. After four months, we analyzed soil physicochemical properties, plant physiological and biochemical responses, biomass, Cd fractionation, plant Cd concentrations, and bioaccumulation factor (BCF). Willow and alfalfa cultivation without Brs increased soil pH and carbonates, reduced the exchangeable Cd fractionation, and increased Cd bound to Fe-Mn oxides and organic matter (p < 0.05). Conversely, Brs application increased soil total acids, increasing the bioavailable Cd (p < 0.05). Willow grown for four months accumulated Cd in leaves, stems, and roots at concentrations of 141.83−242.75, 45.91−89.66, and 26.73−45.68 mg kg−1, respectively, with leaf BCF ranging from 14.53 to 24.88. After five months, leaves of willow planted in Cd-contaminated soil (9.65 mg kg−1) contained 187.90−511.23 mg kg−1 Cd, with BCFs of 19.25−52.38. Brs also increases plant biomass by improving photosynthesis, detoxification, and antioxidant defenses. Treatments with Brs and willow extracted 1.57−1.81 times more Cd (0.56−1.37 mg pot−1) than without Brs (0.31−0.87 mg pot−1). This study offers guidelines for Cd phytoremediation and highlights an effective strategy to enhance Cd accumulation.